ANALISIS TINGKAT RISIKO INVESTASI PADA SAHAM PERBANKAN YANG GO PUBLIC (Studi Kasus pada Saham BBNI dan BNII di Bursa Efek Indonesia Tahun 2007 – 2010) - Wihananto, Adri (Jurnal Ilmiah Binaniaga, 2012)
Indonesia's banking industry experienced ups and downs in recent years. Triggering high inflation volatility of performances and declines of stocks, which greatly affect the performance of Indonesian banks. The increase of stocks indicates the higher interest rates. Higher interest rates could inhibit lending that led to the decline in performance and declines of stocks listed at BEI. Seeing the Indonesian banking industry has not stabilized, the logical consequence faced by investors when deciding to make investments in the banking sector is uncertainty or risk. Risk will always overshadow in any investment decisions taken by investors. This study attempted to compare the level of investment risk from the two banking groups to determine which groups are more risky, so investors could know where a decent investment to be chosen. This study aimed to determine the level of risk groups of state-owned banks, private banks, the level of risk groups by using the trend method, and whether there are differences in risk of both groups.The research methodology used is the descriptive method approach to comparative. The data used is two banking shares listed on the Indonesia Stock Exchange consists of three state-owned bank shares (known as PT. Bank Negara Indonesia Tbk) and private banks (PT. Bank Internasional Indonesia Tbk) during the period 2007 - 2010. The calculation of both the stocks level of risk using standart deviasi, regresion, corelation by using SPSS 17.0 and have statistic test of two parties. From the calculations showed that there was difference in risk between state-owned banks and private banks. With words both state-owned banks and private banks not have the same risk. Due to the influnce of the policies issued by the goverment against the state-owned bank. Result of the statistical tests to PT. Bank Negara Indonesia Tbk. obtained didn’t significant result for the 0.002 with a significance level of 0.05, it can be concluded that there is no influence between the level of risk with the level of returns in the stock of BBNI. Based on the result of statistical tests on significant result obtained PT. Bank Internasional Indonesia Tbk. at 0.05 with a significance level of 0.05, it can be concluded that there is influence between the level of risk with the level of returns in the stock of BNII.Key words: Private Banks, State-owned Bank, the Level of Risk, the Level of Return.